Direct extraction of chitosan from snail shells by natural deep eutectic solvent - Melody, Kimi; Mohd Hazwan, Hamdi (Growing Science, Canada., 2023)
The processes involved to extract chitosan biopolymers from natural resources often employ hazardous chemicals and long processing time. This work provides a sustainable direct extraction method of chitosan from snail shells. Previous attempts using acetogenin in graviola extracts succeeded in the extraction of chitosan from marine shells. However, the slow reaction has prompted the addition of hydrogen bond acceptor solution into the graviola extract. Choline chloride is an excellent hydrogen bond acceptor mixed with acetogenin as hydrogen bond donor to form natural deep eutectic solvent (NADES) for the direct extraction of chitosan. Chitosan obtained from this method has a degree of deacetylation of 91% and a molecular weight of 481 kDa with fiber-like morphology. The direct extraction of chitosan from NADES consisting of choline chloride and acetogenin has proven to extract chitosan with comparable properties to commercial chitosan.